Urban and rural environments differentially shape multisensory perception in ageing - Newell, Fiona; Kenny, Rose (My University, 2021)
Recent studies suggest that the lived environment can affect cognition across the lifespan. We examined, in a large cohort of older adults (n = 3447), whether susceptibility to a multisensory illusion, the Sound-Induced Flash Illusion (SIFI), was influenced by the reported urbanity of current and childhood (at age 14 years) residence. If urban environments help to shape healthy perceptual function, we predicted reduced SIFI susceptibility in urban dwellers. Participants reporting urban, compared with rural, childhood residence were less susceptible to SIFI at longer Stimulus-Onset Asynchronies (SOAs). Those currently residing in urban environments were more susceptible to SIFI at longer SOAs, particularly if they scored low on general cognitive function. These findings held even when controlling for a several covariates, such as age, sex, education, social participation and cognitive ability. Exposure to urban environments in childhood may influence individual differences in perception and offer a multisensory perceptual benefit in older age.
PUBLISHED
cited By 0
Keywords: older age; multisensory illusion; Sound-Induced Flash Illusion (SIFI); older age; multisensory illusion; Sound-Induced Flash Illusion (SIFI); Ageing